Double suicide in modern Japan (in Kanagawa prefecture): Comparison with those in post-war Japan and other countries. (April 2018) - Satoh, Fumiko; Osawa, Motoki
Double-suicide cases have long been common in Japan, particularly among lovers. Classical studies conducted in the 1950s are well known. According to a report by Ohara, the double-suicide rate in Japan was recorded as 3.1% in 1954. Nevertheless, recent tendencies have not been reported. To assess the latest trends of double suicide, extensive studies were conducted in a populous area of Kanagawa, Japan, during 1999–2011. Suicides during the period in the domestic area claimed 23, 195 victims. In all, 82 cases of double suicide were extracted, with 170 victims, meaning that double suicides occurred with incidence of 0.73% among all suicides. The mean age and standard deviation were 51.6±16.1 years, with 83 men and 87 women. The suicide-partner relationships included 40 cases (48.8%) of married couples, 13 (15.9%) of unmarried lovers, and 10 (12.2%) of elderly woman and her son/daughter dyads. No significant difference was found from Western countries in the incidence of double-suicide cases in Japan, except for a higher incidence of suicide involving elderly people and their sons/daughters. The traditional style of double suicide by lovers has become less frequent in modern Japanese society, presumably because of changing marriage styles and values.